Atomic and molecular suite of R-matrix codes for ultrafast dynamics in strong laser fields and electron/positron scattering. Issue 7 (January 2020) - Wragg, J; Benda, J; Mašín, Z; Armstrong, G S J; Clarke, D D A; Brown, A C; Ballance, C; Harvey, A G; Houfek, K; Sunderland, A; Plummer, M; Gorfinkiel, J D; et al.
Synopsis: We describe and illustrate a number of recent developments of the atomic and molecular ab initio R-matrix suites for both time-dependent calculations of ultrafast laser-induced dynamics and time-independent calculations of photoionization and electron scattering.